Website Quality and Personal Branding: Drivers of Satisfaction and Purchase Decision - Lestari, Novia Indah; Sofiati, Nunung Ayu; Parlindungan, Purbanuara; Purwoko, Harry; Wijayanthi, Ida Ayu Trisna (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Digital transformation in commerce has shifted consumer behavior, making website quality and personal branding central factors in shaping customer satisfaction and purchase decisions. While prior studies often analyze these elements separately, limited research has integrated them into a unified framework to explain how digital experiences influence consumer outcomes. This study aims to examine the effects of website quality and personal branding on purchase decisions, with customer satisfaction as a mediating variable. The research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through an online survey of 160 respondents who had prior experience with e-commerce platforms, and the model was tested using SmartPLS with bootstrapping techniques. Findings reveal that website quality positively affects both customer satisfaction and purchase decision, while personal branding significantly influences satisfaction but does not directly impact purchase decision. Moreover, customer satisfaction strongly mediates the relationship between website quality, personal branding, and purchase decision. The study highlights the dual importance of technical excellence and authentic personal branding in fostering satisfaction and driving consumer behavior. The results provide theoretical insights for digital commerce research and practical guidance for businesses to enhance consumer trust, engagement, and purchase outcomes.